Circumscription of Lithophyllum racemus (Corallinales, Rhodophyta) from the western Mediterranean Sea reveals the species Lithophyllum pseudoracemus sp. nov. Issue 6 (1st November 2020) - Caragnano, Annalisa; Rodondi, Graziella; Basso, Daniela; Peña, Viviana; le Gall, Line; Rindi, Fabio
ABSTRACT: Species of the genus Lithophyllum are important carbonate producers and bioconstructors. In recent years, molecular studies focusing on this genus have unravelled several striking cases of cryptic and pseudocryptic diversity. Lithophyllum racemus is a common non-geniculate coralline alga-forming rhodoliths in the northeastern Atlantic Ocean and the Mediterranean Sea. Molecular phylogenies ( psb A and cox I) reconstructed for some Mediterranean specimens morpho-anatomically assigned to L. racemus revealed two well-supported sister clades. Based on pairwise sequence divergences, we recognised these two clades as separate species, L. racemus and L. pseudoracemus sp. nov . The low number of specimens has not permitted any useful morpho-anatomical comparison between the species, and for now, only DNA sequencing permits separation. The discovery of L. pseudoracemus unravelled a new case of cryptic diversity in Mediterranean coralline algae, highlighting the substantially underestimated diversity of these seaweeds.